Stanchion Re-design for Kuala Lumpur Additional Vehicle (KLAV) 27 Project based on SolidWorks Simulation - ROSMI, MOHAMAD ARIF HAKIMI; Mustapha Kamil bin Omran; Mohd Noor Fathullah bin Mohd Noordin (Progress in Engineering Application and Technology, 2023)
Kuala Lumpur Additional Vehicle (KLAV) 27 Project is a project of the Alstom-Hartasuma Consortium (AHC) to supply new Light Rail Transit (LRT) for the Kelana Jaya LRT Line. Each KLAV 27 fleet is equipped with stanchions for passengers to grip and prevent their falling during train motion. However, the problem of the existing stanchion arises during the Kelana Jaya LRT Line collision on 24 May 2021. Many passengers are injured after being hit to the interior equipment including stanchion. Therefore, the objective of this research is to identify the design specifications of the existing stanchion and develops a suitable stanchion that complies with passenger capacity and load specification from Original Equipment Manufacturer (OEM) for KLAV 27 Project. This research also analyses the performance of the new stanchion design. The method for data collection is by doing a literature review, reverse engineering on existing stanchion and survey. The SolidWorks software is used for this project for designing, analyzing and simulating the new stanchion design. The result of this research is proposing a new stanchion design by replacing the existing vertical triple stanchion with a triple horizontal stanchion and adding a horizontal stanchion above the door area. From the result, the new stanchion design has adhered to the load specification of the Original Equipment Manufacturer (OEM) for the KLAV 27 Project and improved the percentage of passengers holding the stanchion by 7.14%. This research is necessary for reference for railway industry players for designing a better stanchion design.